Variability of Bimodal Soil-Water Characteristic Curves under Different Confining Pressures - Achmad Syarifudin; Alfrendo Satyanaga (Applied and Environmental Soil Science)
Soils with two subcurves of Soil-Water Characteristic Curve (SWCC) (dual porosity soils) might be found within various residual soils. Soils located in different depths have different confining pressure. Residual soils are found in the unsaturated zones due to the deep groundwater table. There is a linear correlation between the hydraulic properties of the soil in the unsaturated area and that of its unsaturated properties. This study aims to examine the influence of the confining pressure towards the SWCC of dual porosity soil. The scope of this study involves measurements of the drying and wetting SWCC using Tempe cells, pressure plates, and an advanced triaxial apparatus. In this study, the mathematical equations were developed to explain the effect of confining pressure on SWCC. The experimental results indicated that the dual porosity soil exhibits bimodal characteristics for the drying curve of SWCC and it exhibits unimodal characteristics for the wetting curve of SWCC. As the confining pressure increases, the air entry values, the inflection points, and the standard deviation of drying SWCC increase. In addition, the hysteresis of SWCC is becoming smaller with the increasing confining pressure.